POLA KOMUNIKASI SUAMI ISTRI DALAM MENYELESAIKAN KONFLIK KEHIDUPAN BERUMAH TANGGA DIKENAGARIAN KOTO BERAPAK KECAMATAN BAYANG - Monasari, Yelvi; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2014)
Communication in life is very important that finish conflict in order to keep good relationship. The purpose in this research is to know and describe: 1. Communication pattern of stimulus-respons (S-R) that is used solving the problem by them in home life. 2.  Communication pattern of interactional which is used finishing conflict home life by them at Kenagarian Koto Berapak Kecamatan Bayang.This research is qualitative descriptive research. Informan in this research is husband wife that are include 2 person., and supporting informan 1 parents of wife, 2 friends from husband, 1 friends of wife, 3 person of neighborh. The data of this research is colleted toward interview, observation, and documentation. Real of the data is examined using triangulation data, from the data that is collected then is analyze with interactive model which is consist the data  collection, the data reduction, showing of data and conclusion. The result of this reserach determines that: 1.  Based the result of interview that the researcher does for husband wife and many cases that is not appropriate between partners in home life which create many conflicts in home life at the last, because they are bad relationship to create communication with others in their life. When they are problem, they do not finish soon, because they wait to start saying about the problem happen. 2. Communication pattern of interactional in husband wife finishing conflict home life. Based the researcher got before from interview about communication pattern of interactional determining they have many conflicts in home life and they do not want to finish their problem each others, because they always wait who say first to discuss it. In summary, there are not partner that practice good pattern of interactional communication here what communication pattern which are very good than other communication pattern because this pattern is communication pattern where husband wife are active person without must wait who start saying to finish the conflict firstly.